Strategies and Communications for Innovations An Integrative Management View for Companies and Networks - Hülsmann, Michael; Pfeffermann, Nicole (Springer Berlin Heidelberg, 2011)
The innovation economy sets new standards for global business and requires efficient innovation management to plan, execute and evaluate innovation activities, establish innovative capability and coordinate resources and capacities for innovation on an intra- and inter-organizational level. Moreover, communication of innovation is one essential impact factor of innovation success due to successful launches of innovations into markets, establishment of stakeholder relationships, and strengthened corporate reputation in the long-run. Consequently, the portfolio of communication activities for innovations has to be mastered by a company or collaborative network equal to the innovation portfolio. Thus, management of innovation and innovation communication on a strategic level play an important role in business nowadays. This new book concentrates on new approaches and methods for strategies and communications for innovations. As one part of the book, integrated perspectives on strategy and communication for innovation intend to bridge the gap between innovation management and communication management. This new book shall contribute to management science and answer current question in business. It provides cutting-edge information and offers a knowledge source for researchers, students, and business representatives who design, implement and manage innovation and innovation communication / marketing of innovation.